Women in an art class - Unknown:::Creator::::::::::::
Photograph shows two women sitting at a long table in what may be an art class. The woman on the left has a cake, cards, plates, and napkins in front of her. The woman on the right appears to be painting. There is an easel with a small stretched canvas sitting on it and the table is covered probably to keep paint from getting on it's surface. A large purse sits in front of the easel. A third women is sitting in the background on a bench seat by the windows with a cup in her hands.